Prolonged carriage of (livestock-associated) MRSA in individuals without professional livestock contact. (3rd March 2020) - Meijs, Anouk P; Hengeveld, Paul D; Dierikx, Cindy M; Maassen, Catharina B M; de Greeff, Sabine C; de Haan, Angela; Bosch, Thijs; van Duijkeren, Engeline
Abstract: Objectives: To investigate prolonged carriage of MRSA in adults from the general population living in a livestock-dense area, using WGS. Methods: A cross-sectional study during 2014–15 among 2492 adults without professional livestock contact identified 14 (0.6%) nasal MRSA carriers, 10 of which carried livestock-associated (LA)-MRSA of multiple-locus variable-number tandem repeat analysis (MLVA) complex (MC) 398. Two years later, 12 MRSA-positive and 88 MRSA-negative participants provided a second nasal swab and filled in a short questionnaire. Isolates from persons who were MRSA positive at both timepoints were compared using MLVA and isolates with the same MLVA type were sequenced. The WGS data were used for core-genome MLST (cgMLST) and resistome analysis, including sequenced isolates from the national MRSA surveillance. Results: All MRSA-negative persons tested negative again, while 6 of the 12 initially MRSA-positive persons tested positive again. MLVA revealed that isolate pairs from five individuals had the same MLVA type, of which three were LA-MRSA. cgMLST showed that the distance between these isolate pairs ranged between 3 and 13 genes, while the minimum distance to unrelated isolates from the national MRSA surveillance was 38 genes. Moreover, the resistome present in the five isolate pairs was identical within each pair. None of the prolonged carriers was hospitalized during the 3 months before the sampling moment and none of them with LA-MRSA had contact with livestock in this period. Conclusions: Prolonged carriage of MRSA, including LA-MRSA, can be demonstrated after more than 30 months in persons without professional livestock contact.